2022
DOI: 10.3390/app12042136
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Energy Buildings and Energy Efficiency towards Sustainability: A Bibliometric Review and a Case Study

Abstract: The rapid growth of sustainability has created a plethora of options for expanding zero-energy buildings (ZEBs) and energy efficiency in all aspects of life. In recent years, there has been a rise in interest in ZEBs, and many countries have adopted ZEBs as future energy targets to promote the sustainable development paradigm. The primary goal of this paper was to conduct a bibliometric review of current research on ZEBs and energy efficiency. The first part of this paper identifies new knowledge gaps as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…The solution of zero energy buildings is faced with many challenges including high initial cost, limited incentives, and lack of social awareness (Manzoor et al, 2022). One of the solutions to address these challenges are the American Society for Heating Ventilation and Air Conditioning Engineers (ASHRAE) AEDG achieving 30% and 50% Energy Savings towards a Net Zero Energy Building in addition to their guidelines on achieving zero energy buildings.…”
Section: Ashrae Advanced Energy Design Guidesmentioning
confidence: 99%
“…The solution of zero energy buildings is faced with many challenges including high initial cost, limited incentives, and lack of social awareness (Manzoor et al, 2022). One of the solutions to address these challenges are the American Society for Heating Ventilation and Air Conditioning Engineers (ASHRAE) AEDG achieving 30% and 50% Energy Savings towards a Net Zero Energy Building in addition to their guidelines on achieving zero energy buildings.…”
Section: Ashrae Advanced Energy Design Guidesmentioning
confidence: 99%
“…As the number of new buildings developed in China continues to grow, failure to effectively reduce the energy consumption and carbon emissions of the building sector will hinder the attainment of the energy efficiency and low-carbon development goals set in the country [6]. Thus, there is a need to promote energy efficiency and renewable energy use in buildings, to move further towards near-zero energy consumption [7]. This will aid in addressing energy and environmental goals and is a prerequisite to dealing with climate change.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research is being conducted in this direction, both around the world and in Poland. Bibliometric analysis of 2592 articles conducted by Bibal Manzoor and others (with the use of the Scopus database) showed that there are 252 publications in the field of the energy efficiency of buildings with regards to sustainability [5]. An important role in this transformation is played by the change in the approach and mentality of architects regarding designing in the old formula and also their transition to an integrated design process [6][7][8].…”
Section: Introductionmentioning
confidence: 99%